2023
DOI: 10.1038/s41746-023-00828-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of performance of wearable artificial intelligence in detecting and predicting depression

Abstract: Given the limitations of traditional approaches, wearable artificial intelligence (AI) is one of the technologies that have been exploited to detect or predict depression. The current review aimed at examining the performance of wearable AI in detecting and predicting depression. The search sources in this systematic review were 8 electronic databases. Study selection, data extraction, and risk of bias assessment were carried out by two reviewers independently. The extracted results were synthesized narrativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 76 publications
3
4
4
Order By: Relevance
“…To elaborate, although the pooled mean in this review was 85.6%, the average accuracy estimates in the previous reviews were 87.6% (50%-100%) [ 28 ], 87% (70.8%-99%) [ 34 ], 86% (60%-100%) [ 15 ], 85.4% (64.5%-98.3%) [ 35 ], 84.2% (51.2%-100%) [ 24 ], and 82.9% (53%-99%) [ 13 ]. Furthermore, this review showed findings comparable with those of previous studies on the performance of wearable AI in detecting depression [ 74 ] and anxiety [ 75 ]. Specifically, the pooled mean accuracies of wearable AI in detecting depression and anxiety were 89% [ 74 ] and 82% [ 75 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To elaborate, although the pooled mean in this review was 85.6%, the average accuracy estimates in the previous reviews were 87.6% (50%-100%) [ 28 ], 87% (70.8%-99%) [ 34 ], 86% (60%-100%) [ 15 ], 85.4% (64.5%-98.3%) [ 35 ], 84.2% (51.2%-100%) [ 24 ], and 82.9% (53%-99%) [ 13 ]. Furthermore, this review showed findings comparable with those of previous studies on the performance of wearable AI in detecting depression [ 74 ] and anxiety [ 75 ]. Specifically, the pooled mean accuracies of wearable AI in detecting depression and anxiety were 89% [ 74 ] and 82% [ 75 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, this review showed findings comparable with those of previous studies on the performance of wearable AI in detecting depression [ 74 ] and anxiety [ 75 ]. Specifically, the pooled mean accuracies of wearable AI in detecting depression and anxiety were 89% [ 74 ] and 82% [ 75 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
“…To address this gap, this review aimed to examine the performance of wearable AI in detecting and predicting anxiety. It is worth noting that this review is built upon and differs from our previous reviews [22,23]. Specifically, the first study [22] was a scoping review to explore the features of wearable AI used for anxiety and depression and identify the research gaps in this area.…”
Section: Research Problem and Aimmentioning
confidence: 99%
“…smartwatches) could enable continuous monitoring of (bio)markers and signals as well as environmental influences, which could help to overcome traditional assessment limitations and detect signs of depression in real time. This combination could help improve the accuracy and timeliness of mental health monitoring and enable individuals to proactively maintain their wellbeing [14,15].…”
Section: Use Case 2: Virtual Therapy Assistant (Vta)mentioning
confidence: 99%